The Effect of the Think-Pair-Share and Problem-Based Learning Models on the Indonesian Language Learning Outcomes of Fifth-Grade Students at SDN 169 Sadar: Pengaruh Model Think Pair Share dan Problem Based Learning terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas V SDN 169 Sadar - Nur Hikmah; Rahma Ashari Hamzah; Abdul Wahid (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Penelitian ini bertujuan untuk menelaah pengaruh model pembelajaran think pair share dan model pembelajaran problem based learning terhadap hasil belajar pada mata pelajaran Bahasa Indonesia siswa kelas V SDN 169 Sadar Kabupaten Bone. Metode penelitian yang digunakan adalah metode kuantitatif eksperimen dengan desain one group pretest posttest dengan sampel 15 siswa. Data dikumpulkan melalui observasi, dokumentasi, dan lembar tes, serta pretest dan posttest. Hasil penelitian menunjukkan peningkatan keterlibatan siswa dalam menerapkan model pembelajaran, tercermin dari meningkatnya aktivitas, kerja sama antar kelompok. Nilai posttest juga mengalami peningkatan signifikan dibandingkan pretest, diperkuat oleh hasil uji normalitas dan uji homogenitas. Secara umum, model pembelajaran think pair share dan model pembelajaran problem based learning efektif dalam meningkatkan pemahaman siswa terutama pada mata pelajaran Bahasa Indonesia. This study aims to determine the effect of the think pair share and problem based learning models on the Indonesian language learning outcomes of fifth-grade students at SDN 169 Sadar. The research design used is a non-equivalent control group design. The research sample was 15 people. Data collection techniques were tests, observation and documentation. The results of descriptive analysis obtained that the Indonesian language learning outcomes of students before the use of the think pair share and problem based learning models were in the sufficient category with a frequency of 1 student (6.66%) with an average value of 60-69. While the Indonesian language learning outcomes after the use of the think pair share and problem based learning models were in the very good category with a frequency of 14 students (93.33%) with an average value of 90-100. Thus, it can be concluded that there is a significant influence of the use of the think pair share and problem based learning models on the Indonesian language learning outcomes of fifth-grade students at SDN 169 Sadar as evidenced by a significance value of 0.003 with a significance level of 0.05.